2017
DOI: 10.1007/s11010-017-3093-y
|View full text |Cite
|
Sign up to set email alerts
|

Lead enhancement of 3T3-L1 fibroblasts differentiation to adipocytes involves ERK, C/EBPβ and PPARγ activation

Abstract: Lead (Pb) is an environmental and industrial contaminant that still represents a public health problem. Elevated Pb exposure has been inversely correlated with femoral bone density and associated with osteoporosis. In the last years, it has been shown that inhibition of osteogenesis from mesenchymal stem cells activates adipogenesis and vice versa. In this paper, we investigated the effect of Pb on the differentiation of 3T3-L1 fibroblasts to adipocytes which is the cell model most used to study adipogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…is process was further characterized by an inhibition of the cellular signaling pathway of Wnt/β-catenin. More recently, the proadipogenic effect of lead was demonstrated in 3T3-L1 cultures, which involved the activation of the ERK, C/EBPβ, and PPARc pathways [86].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…is process was further characterized by an inhibition of the cellular signaling pathway of Wnt/β-catenin. More recently, the proadipogenic effect of lead was demonstrated in 3T3-L1 cultures, which involved the activation of the ERK, C/EBPβ, and PPARc pathways [86].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…This may be the mechanism by which NP causes the onset of type II DM and NAFLD. Results of the measurement of lipid metabolism-related protein levels revealed that NP exposure promoted the expression of the lipid-metabolism-related proteins C/EBPα, FAS, PPARγ, and SREBP1 in 3T3-L1 preadipocytes [32,33]. These proteins play key roles in the proliferation, differentiation, maturation, and lipid metabolism of adipocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…During this process, the expression of adipogenic transcription factors, including PPAR γ , C/EBP α , and SREBP1 is stimulated [35]. C/EBP β is expressed earlier during adipogenesis because it is required for the induction of MCE caused by MDI medium [36] and then triggers the expression of PPAR γ and C/EBP α in 3T3-L1 cells [37]. The data showed that Bugi markedly suppressed the PPAR γ , C/EBP α , and SREBP1 expression on Day 4 but also C/EBP β expression on Day 2 in differentiated 3T3-L1 cells (Figures 1(e) and 1(f)).…”
Section: Discussionmentioning
confidence: 99%